Socioeconomic Factor Association to Knowledge and Attitude of Indonesian Young Adults Regarding Family Planning: A Cross-Sectional Multicenter Study - Setiawan, Fajar; Megantari, Ginaung Sasti; Setia Santoso, Laurentia Fidella Averina; Nurdiansyah, Farhan; Salsabiil, Ronaa; Mallapasi, Hajar Azizah Armarani; Latifi, Sophie Romzia (Journal of Maternal and Child Health, 2025)
Background: Young adults are prone to unwanted pregnancy due to their nature of self-discovery, identity construction, poor knowledge, and low birth self-efficacy. This study aims to identify which socioeconomic factors are associated with knowledge and attitude toward family planning in Indonesian young adults. Subjects and Method:  This cross-sectional, observational, multicenter research was conducted in 27 universities across Java and Sumatra using convenience sampling. Indonesian citizens aged 16–25 were recruited to complete an online questionnaire, with minimum sample size of 349 participants. The dependent variable were knowledge and attitude levels were measured using translated and validated questionnaire. The independent variable were socioeconomic factors were assessed using self-administered questionnaire. Chi-square and odds ratio were used to identify significant associations, followed by logistic regression for independent analysis. Results: From total of 581 participants, knowledge of family planning was significantly higher in females (OR= 1.50; p= 0.036), married respondents (OR= 0.20; p <0.001), those with children (OR= 2.12; p= 0.040), contraceptive users (OR= 0.49; p = 0.043), respondents from health-related backgrounds (OR= 2.82; p <0.001), and those with higher media exposure (OR= 4.29; p <0.001).Among these, respondents using contraception (OR= 0.48; p= 0.033) and with higher media exposure (OR= 1.63; p=0.017) demonstrated more favorable attitudes toward family planning. Conclusion: This study identified media exposure and access to education as key factors influencing knowledge and attitudes toward family planning. In the globalization era, media exposure has the potential to dismantle entrenched socioeconomic barriers, narrowing gaps between privileged and disadvantaged groups. These findings highlight the role of social media as an important educational tool that can bridge demographic and socioeconomic divides.